The Marginal and Aerage Propensities to Consume: Reply - Hubbard, J. C. (Quarterly Journal of Economics, 1955)
Journal Article The Marginal and Average Propensities to Consume: Reply Get access J. C. Hubbard J. C. Hubbard Bryn Mawr College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Page 647, https://doi.org/10.2307/1882005 Published: 01 November 1955